Pharmacy program to improve care for veterans with transient ischaemic attack: a pilot implementation evaluation. Issue 3 (8th September 2022) - Rattray, Nicholas; Damush, Teresa M; Myers, Laura; Perkins, Anthony J; Homoya, Barbara; Knefelkamp, Christopher; Fleming, Breanne; Kingsolver, Andrea; Boldt, Amy; Ferguson, Jared; Zillich, Alan; Bravata, Dawn M
Abstract : Background: Early evaluation and effective communication to manage transient ischaemic attacks (TIA) may lead to a reduction of up to 70% in recurrent events for patients with TIA/minor stroke, along with reduced costs and lengths of hospital stay. Methods: We conducted a single site pilot evaluation of a clinical pharmacy programme to improve medication management among TIA patients. The programme included a structured protocol, online identification tool, and a templated discharge checklist. Primary effectiveness measures were change in systolic blood pressure (SBP) 90 days post discharge and prescription of high/moderate potency statins. Contextual aspects and clinical perspectives on the implementation process were evaluated through prospective semistructured interviews with key informants. Results: The analysis included 75 patients in the preimplementation group and 61 in the postimplementation group. The mean SBP at 90 days post discharge was significantly lower in the post implementation period (pre implementation, 133.3 mm Hg (SD 17.8) vs post implementation, 126.8 mm Hg (16.6); p=0.045). The change in SBP from discharge to 90 days post discharge was greater in the postimplementation period (15.8 mm Hg (20.5) vs 24.8 mm Hg (23.2); p=0.029). The prescription of high/moderate potency statins were similar across groups (pre implementation, 66.7% vs post implementation, 77.4%; p=0.229). Front-line clinicians involved in the pilot study reported positively on the acceptability, appropriateness and feasibility of implementing the protocol without additional cost and within current scope of practice. Conclusions: Implementation of a clinical protocol outlining medication management and provider communication to ensure rapid postdischarge treatment of TIA patients was associated with SBP improvements. The pilot evaluation demonstrates how clinical pharmacists may play a role in treating low frequency, high stakes cerebrovascular events where early treatment and follow-up are critical.